2018
DOI: 10.1007/s11540-018-9398-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Selected Insecticides and Natural Preparations Against Leptinotarsa decemlineata

Abstract: A field experiment was carried out to evaluate the effectiveness of synthetic and natural preparations in protecting potato against Leptinotarsa decemlineata (Colorado Potato Beetle). Seven substances and microorganisms with proved or potential toxic effect on the pest were used: Neem extract (Azadirachta indica), suspensions of Beauveria bassiana Balsamo (Vuillemin) (Hypocreales: Cordycipitaceae) and Isaria fumosorosea Wize (Hypocreales: Cordycipitaceae) entomopathogenic fungal spores, natural pyrethrin and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The efficacy of neem oil was very good even at low concentrations such as 0.1-2 g•L −1 in our bioassays. The efficacy of neem products may vary with respect to concentrations of azadirachtin [38], and thus some authors have stated lower insecticidal activity against CPB [39,40]. However, that was not the case in our study, because the commercial product NeemAzal T/S (Trifolio-M GmbH, Lahnau, Germany) used in the bioassay contains 1% of the purified active ingredient Azadirachtin A, which is a very potent insect growth inhibitor [41] (reviewed in [19,42]).…”
Section: Discussionmentioning
confidence: 65%
“…The efficacy of neem oil was very good even at low concentrations such as 0.1-2 g•L −1 in our bioassays. The efficacy of neem products may vary with respect to concentrations of azadirachtin [38], and thus some authors have stated lower insecticidal activity against CPB [39,40]. However, that was not the case in our study, because the commercial product NeemAzal T/S (Trifolio-M GmbH, Lahnau, Germany) used in the bioassay contains 1% of the purified active ingredient Azadirachtin A, which is a very potent insect growth inhibitor [41] (reviewed in [19,42]).…”
Section: Discussionmentioning
confidence: 65%
“…Several field trials demonstrated a good potential of B. bassiana to control CPB [32][33][34][35][36]56]. Biocontrol agents are usually applied in the field as a spray, while we used dip test in our laboratory assays.…”
Section: Discussionmentioning
confidence: 99%
“…Strain CCM 8367 of this species isolated from Cameraria ohridella, Deschka and Dimić (Lepidoptera: Gracillariidae) [29][30][31] caused high mortality against CPB larvae under laboratory conditions [19]. Field trials of another study revealed that potato plots treated with I. fumosorosea or B. bassiana had significantly higher tuber yield compared to an untreated control but still lower than the yield obtained from the plots protected with chemical pesticides [32]. Similar results were obtained in small field plot experiments in the USA [33].…”
Section: Introductionmentioning
confidence: 99%
“…As known, the lethal effects of EPF and EPN on L. decemlineata are higher, especially in pre-adult stages (Ropek and Kołodziejczyk 2018). Use of the entomopathogenic organisms on the pupal stage of this pest has not been studied.…”
Section: Introductionmentioning
confidence: 99%